Perceived Public Service Quality and Accessibility for Regional Index Development: The Case of City of Mojokerto-Indonesia - Abdullah Said (HABITAT, 2022)
This research focuses on health and education as basic needs to build society through public services. Quality and accessibility are a series of processes to provide valuable services to society as a whole. Additionally, there is regional development to be closer and reach the community to avoid imbalances that occur between regions. This study used survey data collection methods and data analysis using quantitative descriptive. The sample of this study was 195 respondents spread across three districts of the City of Mojokerto using stratified random sampling related to a proportional sample. The findings in this study indicate that public services affected the quality and accessibility improvement of the people of Mojokerto Regency. However, public perception still showed that public services are not yet quality and affordable in all areas of society. Thus, public services have not been felt with the ease of access in some areas. There needs to be an evaluation of public services to provide welfare and improve connectivity between regions.